ประสบการณ์การดูแลตนเองในการป้องกันการหกล้มซ้ำของผู้สูงอายุ - กนกพร สมตระกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The objective of this qualitative research was to describe the elderly’s self-care experiences in preventing recurring falls following Martin Heidegger’s Phenomenology Interpretive Approach.  Twelve elderly subjects were selected according to purposive sampling who had not experienced a fall during the past year before participating in the study.  In-depth interviews were conducted and the interview sessions were recorded.  Then, the data were transcribed and analyzed based on Benner’s approach (1985).The findings indicated that the elderly subjects agreed with the following 5 statements: 1) The falls were caused by carelessness; however, they sometimes involved hard luck; 2) Because of the strong emotions associated will falls, the subjects did not want to experience any more.  Such emotions included panic, confusion, numbness, pain and fear that they would have to depend on others during recovery or after; 3) After the fall, they were able to assess their condition immediately before seeking medical treatment; 4) After the fall, they were more attentive to what they were doing or able to avoid situations that could lead to a fall, and 5) The subject’s family members were able to help prevent them from falling by taking proper care and modifying the house to suit their physical limitations.Healthcare personnel can apply the findings of the study to assist the elderly and their family members in understanding what to do to prevent recurring falls.